Analysis of Intertextual Relationships of Allusions in Mirza Mohammad Seil Akhbāri’s Divan (Manuscripts) - Maryam Jalalvand; Zahra Ghoroghi; Gholamreza Davoodipour (مطالعات زبانی و بلاغی)
Intertextual studies are among the important approaches in contemporary literary research. According to the theory of intertextuality, no text exists without a pre-text, and texts are continuously recreated or reinterpreted based on earlier texts. Considering allusion as exemplar of intertextuality, the purpose of this study is to analyze the intertextual relationships of allusions in the poetry of Mirza Mohammad Seil Akhbāri using a descriptive-analytical method. The results of this study indicate that allusions in Seil Akhbāri's poetry are often connected to literary romanticism, mythological themes, religious subjects, and religious figures. Intertextual relationships in the works of this poet are based on the three types of Kristeva's transtextuality - partial negation, parallel negation, and complete negation, among which, partial negation is more prevalent and shows the highest rate of frequency in the poetry of Seil Akhbāri.